Optimización del Uso del Agua de bebida en la Crianza de Pollos de Carne en la etapa de inicio mediante el uso de un bebedero lineal artesanal. - Chuquista Julca, Danny Enrique (2012)
This paper titled "Optimizing the use of drinking water in rearing broilers in the initiation stage by using a linear scale trough", aimed to the validation of the use of a linear trough craft Broiler chicken boot stage (0-21 days), determine the production indices of broilers at initial stage (0-21 days), such as weight gain, feed conversion efficiency of utilization of drinking water and profitability, raised on two types of drinkers, cone and linear scale and evaluate drinking water consumption of broilers in the initial stage (0-21 days) in the tropical climate of San Martín, using two supply systems drinking water, drinking cone (Traditional) and linear scale trough (innovating). Developed in the academic center of agricultural production "Miraflores", Faculty of Agricultural Sciences, National University of San Martin-Tarapoto, Ahuashiyacu Sector, District Band Shilcayo, Province and Department of San Martín. The methodology was developed for three weeks for the initial stage of a batch of six hundred line broilers Cobb Mixed (50% males and 50% females), we evaluated the effect of two systems of drinking water supply: sprue sprue cone and linear scale. The conclusions were: The biological response in terms of production rates (weight gain and feed conversion) obtained have not undergone greater variation effect of using two types of treatment troughs at T1 (Bebedero linear scale) and T0 (Bebedero traditional cone) in raising broilers in the initial stage (0-21 days). Water consumption in the T1 (linear scale drinker) with an average of 17.56 liters in the third week was higher than the control T0 (Bebedero cone) which reported a water consumption of 19.92 in the third week, this may be reflected in the greater weight gain obtained in treatment T1 (linear scale drinker) with an average of 771.80 g compared to the control T0 (Bebedero cone) obtained an average of 751.20 g of body weight. Water wastage in the three weeks was extensively evaluated lower in the treatment T1 (linear scale drinker) with 0.77 liters in the first week, 0.23 in the second week and 0.29 liters in the third week, regarding the extensive loss of water T0 treatment (trough) that has received the most waste water with an average of 20.68 liters in the first week, 15.72 liters in the second week and 9.91 liters in the third week. The use of traditional linear trough (T1), generated greater economic benefits in raising broilers in the initial stage (0-21 days) reporting a net return of 28.34% compared to 23.24% of net profit obtained with the use of linear feeder craft.